The Influences of Slack Resources, Board Gender Diversity on the Quality of Corporate Social Responsibility Disclosure - Merdianeu Utami Putri; Harry Suharman; Sofik Handoyo (PT Mattawang Mediatama Solution, 2023)
This study aims to examine the effect of slack resources and board gender diversity on the quality of corporate social responsibility disclosure. This study also examines the board's moderating role of gender diversity on slack resources and the quality of corporate social responsibility disclosure. The analysis of this research uses the panel data analysis method. The research sample consisted of 44 companies listed on the IDX and published sustainability reports during the 2018-2019 period. The results of the study found that board gender diversity on the board of commissioners has a negative effect on the quality of corporate social responsibility disclosure. Slack resources and board gender diversity of directors are proven to have no effect on the quality of corporate social responsibility disclosure. The results also show that the gender diversity board does not moderate the relationship between slack resources and the quality of corporate social responsibility disclosure. This is due to the low proportion of women in the board structure of public companies in Indonesia